Neurocysticercosis : A Case Report - Biswas, Rajat Sanker Roy; Nath, Jishu Deb (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Cysticercosis is a common tropical disease though rare in Bangladesh. One of the common manifestations of cysticercosis is Neurocysticercosis (NCC). We report an immunocompetent patient with neurocysticercosis. He was otherwise asymptomatic in spite of the extensive involvement of central nervous system. A planned approach to therapy is necessary to prevent further deterioration. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22886 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 59-60